Associations of Patient Experience With Doctor-Patient Communication and Patient-Reported Physical and Mental Health in Seriously Ill Adults - Sarah F. D’Ambruoso MSN; Anne M. Walling MD, PhD; Neil S. Wenger MD, MPH; Rebecca L. Sudore MD; Lisa Gibbs MD; Maryam Rahimi MD; Ron D. Hays PhD (Journal of Patient Experience)
The importance of effective doctor-patient communication is well established; however, rigorous evaluations of its association with patient-reported outcomes among seriously ill patients are needed. We analyzed 2 waves of survey data from adults with serious illnesses in primary care clinics. We administered the Consumer Assessment of Healthcare Providers and Systems (CAHPS ® ) communication scale, Patient-Reported Outcomes Measurement and Information System (PROMIS ® ) global health items, and the PROMIS-29 depression and anxiety scales. We evaluated a structural equation model to assess relationships between patient experience and self-reported global physical and mental health in 779 patients at baseline and 12 months later. Average age was 69, with 52% male, 18% Hispanic, 9% Asian, and 7% Black; 24% had a high school education or less. Better global health (PROMIS) at baseline was associated with better doctor-patient communication (CAHPS) at 12 months (β = 0.09, P  = .005), and better doctor-patient communication at baseline was related to better mental health at follow-up (β = 0.07, P  = .0105). The results suggest that patients’ overall health may influence doctor-patient communication, and this communication may impact patients’ mental health over time.